1978
DOI: 10.1111/j.1600-0528.1978.tb01168.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dental caries among workers in the sweets industry in Israel

Abstract: The purpose of the present study was to assemble data on the prevalence of dental caries among workers in the sweets industry. Four industrial establishments were selected for the study. All production-line workers were included. Altogether 722 participants. The control group consisted of a group of production-line workers in five textile industrial establishments, altogether 812 examinees. The results indicate that the mean DMFT values recorded for the sweets industry workers were significantly higher than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
2
1

Year Published

1980
1980
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 4 publications
(1 reference statement)
1
9
2
1
Order By: Relevance
“…Still the prevalence of FT was statistically diminishing with increasing age groups because of false belief of extraction rather than restoration in older age groups. However, finding of the study conducted by Anaise [20] among workers of sweet industry in Israel demonstrated the highest FT (5.21 ± 2.76) among 30-39 years age group, which was in contrast with the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…Still the prevalence of FT was statistically diminishing with increasing age groups because of false belief of extraction rather than restoration in older age groups. However, finding of the study conducted by Anaise [20] among workers of sweet industry in Israel demonstrated the highest FT (5.21 ± 2.76) among 30-39 years age group, which was in contrast with the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…This is agreement with the findings of Peterson PE, Frencken JE, et al, Anaise JZ Budner L [3,5,11,12]. However, the findings were quite low as compared to the findings of Bachanek T et al, who reported Mean D.M.F.T among flour mill workers to be 17.77 [2].…”
Section: Resultssupporting
confidence: 55%
“…Examples of this trend include populations in the Inuit in Alaska, USA 63 as well as populations in Ethiopia There is evidence to show that many groups of people with habitually high consumption of sugars also have levels of caries higher than the population average, for example, children with chronic diseases requiring longterm sugar-containing medicines 69 . Environmental exposure to high sugars has also been studied: Anaise 70 found that confectionery industry workers had 71% higher dental caries experience than factory workers from other industries. Katayama 71 also found higher caries in confectionery workers (DMFT 17.2) compared with workers in other industries (DMFT 11.4).…”
Section: Dental Caries Patterns Following Changes In Availability Of mentioning
confidence: 99%